The European venture capital landscape: an EIF perspective. Volume IV: The value of innovation for EIF-backed startups - Simone Signore; Wouter Torfs (European Investment Fund (EIF), 2017)
The creation of value through innovation is among the defining traits of new technology-driven ventures. In this paper we contribute to the literature by investigating the value of innovations for start-ups supported by EIF in the years 1996 to 2014, as measured through patent applications. The paper is structured around two main parts. The first part presents a series of descriptive statistics on EIF's VC investee patent portfolio and discusses some of the strategic aspects of patenting, such as timing and geographical coverage. The second part develops an econometric model to estimate the Euro-value of innovations based on patent renewal data, following the seminal work of Pakes and Schankerman (1984). We observe that start-ups are efficient at transforming financial capital obtained through VC financing into innovative capital. On average, for every Euro of EIF-supported VC financing, start-ups generated 2.74 Euro of private innovation value.
Keywords: G24; M13; O32; 330; EIF; venture capital; innovation; patents; renewal data; start-ups